A novel colorimetric fluorescent probe for detecting hydrazine in living cells and zebrafish. (24th April 2022) - Zhao, Zhenhua; Xing, Liting; Feng, Quanlin; Han, Lin
Abstract: Hydrazine (NH2 NH2 ) is a highly toxic organic substance that poses a threat to human health. Monitoring hydrazine with high sensitivity and selectivity is very important. Here, a simple colorimetric fluorescent probe for hydrazine detection, which is a seminaphthorhodafluor derivative containing thiophene‐2‐carboxylic acid ester reaction site, was rationally constructed. The probe itself exhibits weak fluorescence. The fluorescence is significantly enhanced when hydrazine is added. The probe exhibited a broad linear range (0–1 mM) with satisfactory selectivity and sensitivity (limit of detection 36.4 μM), which turned out to be an excellent fluorescent probe for monitoring hydrazine. Additionally, the probe was used to track hydrazine in living cells and zebrafish with great success, and the detection performance was satisfying. These results proved that this type of fluorescent probe with the thiophene‐2‐carboxylic acid ester structure can detect hydrazine with higher selectivity and sensitivity. Abstract : A novel seminaphthorhodafluor‐based colorimetric and far‐red fluorescent probe for monitoring hydrazine was rationally designed and synthesized. This probe can provide a promising analytical technique for monitoring hydrazine in the environment and biological systems.